Venture Capital Law Renewal: A Solution for Business Convenience and Legal Certainty in Indonesia - Adhie, Aryasatya Justicio; Suwandono, Agus; Yuanitasari, Deviana (Jambura Law Review, 2023)
Investing, for example, using venture funds, can now be done easily.  Venture funds are raised by venture capital companies and given to investee companies. Problems can arise when the venture capital company does not have a license to operate but carries out activities as if it has a permit. Of course, this can have legal consequences for venture fund investors, investee companies, and venture capital companies. Another problem concerns the legal certainty of venture capital companies for foreigners who wish to invest in Indonesia; foreigners need to be able to judge the appropriateness of the legal products governing venture capital companies. This article is intended to determine the legal consequences facing unlicensed venture capital companies and the legal certainty for foreign investors. This research method uses a normative juridical method by conducting a literature study on the provisions of venture capital companies in Indonesia. Article VCC in Indonesia has contributed to the Indonesian economy by helping businesses grow. However, this growth must be in line with the harmonization of regulations regarding venture law and investment in Indonesia in order to provide legal certainty to prospective investors.